Vertical School, Dwarka, Delhi - Bansal, Priya (SPA Bhopal, 2020)
This paper analyses the changing school model in the country. Under the government policies to provide education for all till 8th std., there exists a shortage of schools in the country for primary and upper primary education. This shortage has become increasingly evident in the country with land shortage and increased migration to city centres. City centres are attractive as they provide easy access to all types of infrastructure. Schools form an important part of any community irrespective of their size or type. To satisfy the need for education, small schools are scattered all over the cities. Due to the increased number of these small schools, the government has tried to enforce the policies to consolidate these schools as these small schools have higher dropout rates due to lack of infrastructure and also a majority of these schools are only for primary students. The design thesis focuses on to understand the transition from traditional schools to vertical schools. The study intends to understand and analyse schools with five floors and more to understand the spatial organisation and design strategies used to create an environment which in no manner compromises with the all-round and holistic development of a child in comparison to that of traditional schools.
Keywords: vertical school; land shortage; teaching pedagogy; classroom